2022
DOI: 10.1039/d2cc03367d
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species-responsive Pre-PROTAC for tumor-specific protein degradation

Abstract: By introducing a Reactive oxygen species (ROS) triggered leaving group (arylboronic acid) to the parent PROTACs. ROS-responsive Pre-PROTACs were designed and evaluated. Pre-PROTAC (7) efficiently degrade the target proteins BRD3...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Liu et al. also reported PROTACs activated by ROS 122 (Figure 6C). They constructed ROS‐PROTAC by introducing arylboronic acid into the parental PROTACs and observed that it could be activated by endogenous ROS and effectively degrade the target protein BRD3.…”
Section: Precision Guidance: Regulatory Activation and Targeted Deliverymentioning
confidence: 62%
See 1 more Smart Citation
“…Liu et al. also reported PROTACs activated by ROS 122 (Figure 6C). They constructed ROS‐PROTAC by introducing arylboronic acid into the parental PROTACs and observed that it could be activated by endogenous ROS and effectively degrade the target protein BRD3.…”
Section: Precision Guidance: Regulatory Activation and Targeted Deliverymentioning
confidence: 62%
“…(A) AP‐PROTAC is more active at trans ‐configuration and can be converted to 99% cis‐isomers under 365 nm UV irradiation. Therefore it can be easily regulated; 115 (B) Only by discarding the HALG with the help of hypoxia conditions can the Ha‐PROTAC be activated, or HALG is going to hinder EGFR from being targeted; 116 (C) ROS is able to remove arylboronic acid which blocks E3 ligase from the PROTAC and activate it, therefore induces BRD4 degradation; 122 (D) The regulation of PROTAC can also be regulated by enzyme‐catalyzed activation. With the help of overexpressed NQO1 in cancer cells, Caged‐PROTAC will be released and activated 119 …”
Section: Precision Guidance: Regulatory Activation and Targeted Deliverymentioning
confidence: 99%
“…In contrast, although glutarimide nitrogen of the CRBN binder can serve as a chemical handle in some cases, unexpected problems may occur due to incomplete cleavage and poor stability. 35,53 Indeed, there are still many other MOAs that can be employed for the development of tumor-targeting PROTACs. Using similar strategies, it is possible to develop pro-PROTACs for treating diseases other than cancer.…”
Section: Discussionmentioning
confidence: 99%
“…52 Liu et al developed a class of ROS-responsive PROTACs recruiting CRBN E3 ligase for selective degradation of BRD3. 53 Prodrug 32 (Figure 7B) was obtained by installing aryl boronic acid on the aromatic amine group of the lenalidomide fragment. When treated with H 2 O 2 , aryl boronic acid-caged pro-PROTAC 32 was converted to a phenolderived intermediate and underwent subsequent 1,6-benzyl elimination to release the active PROTAC.…”
Section: Pro-protacs Activated By Other Moasmentioning
confidence: 99%
“…Low ROS levels are maintained in normal cells, while it is much higher in the tumor microenvironment [ 32 ]. Chen et al (2022) designed ROS-responsive Pre-PROTACs 3 by conjugating an ROS-triggered leaving group, arylboronic acid, to the parent PROTACs [ 33 ]. This PROTAC molecule 3 was designed by recruiting a CRBN ligand and BRD3 protein ligand to opposite ends connected by varying linkers ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%